Study guides

☆☆

Q: What is the sum of x-3 and 2x plus 7?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

(x3 + 3x2 - 2x + 7)/(x + 1) = x2 + 2x - 4 + 11/(x + 1)(multiply x + 1 by x2, and subtract the product from the dividend)1. x2(x + 1) = x3 + x22. (x3 + 3x2 - 2x + 7) - (x3 + x2) = x3 + 3x2 - 2x + 7 - x3 - x2 = 2x2 - 2x + 7(multiply x + 1 by 2x, and subtract the product from 2x2 - 2x + 7)1. 2x(x + 1) = 2x2 + 2x2. (2x2 - 2x + 7) - (2x2 + 2x) = 2x2 - 2x + 7 - 2x2 - 2x = -4x + 7(multiply x + 1 by -4, and subtract the product from -4x + 7)1. -4(x + 1) = -4x - 42. -4x + 7 - (-4x - 4) = -4x + 7 + 4x + 4 = 11(remainder)

7 x3 + 2 x = x (7 x2 + 2)

2x+7=n

4x2 + 28x + 49 = 4x2 + 14x + 14x + 49 = 2x(2x + 7) + 7(2x + 7) = (2x + 7)(2x + 7) or (2x + 7)2

14

Related questions

(x3 + 3x2 - 2x + 7)/(x + 1) = x2 + 2x - 4 + 11/(x + 1)(multiply x + 1 by x2, and subtract the product from the dividend)1. x2(x + 1) = x3 + x22. (x3 + 3x2 - 2x + 7) - (x3 + x2) = x3 + 3x2 - 2x + 7 - x3 - x2 = 2x2 - 2x + 7(multiply x + 1 by 2x, and subtract the product from 2x2 - 2x + 7)1. 2x(x + 1) = 2x2 + 2x2. (2x2 - 2x + 7) - (2x2 + 2x) = 2x2 - 2x + 7 - 2x2 - 2x = -4x + 7(multiply x + 1 by -4, and subtract the product from -4x + 7)1. -4(x + 1) = -4x - 42. -4x + 7 - (-4x - 4) = -4x + 7 + 4x + 4 = 11(remainder)

That depends on whether or not 2x is a plus or a minus

== == Suppose f(x) = x3 + 3x2 - 2x + 7 divisor is x + 1 = x - (-1); so rem = f(-1) = 11

7 x3 + 2 x = x (7 x2 + 2)

x3 + 2x2 - 35x = x(x2 + 2x - 35) = x(x + 7)(x - 5)

2x+7=n

2x3 - 7 + 5x - x3 + 3x - x3 = 8x - 7

Sum Numb!

4x2 + 28x + 49 = 4x2 + 14x + 14x + 49 = 2x(2x + 7) + 7(2x + 7) = (2x + 7)(2x + 7) or (2x + 7)2

2x + 7

2x = -7 - 8y

14

People also asked